2013
DOI: 10.1007/s10545-013-9618-y
|View full text |Cite
|
Sign up to set email alerts
|

The neuropsychiatry of inborn errors of metabolism

Abstract: A number of metabolic disorders that affect the central nervous system can present in childhood, adolescence or adulthood as a phenocopy of a major psychiatric syndrome such as psychosis, depression, anxiety or mania. An understanding and awareness of secondary syndromes in metabolic disorders is of great importance as it can lead to the early diagnosis of such disorders. Many of these metabolic disorders are progressive and may have illness-modifying treatments available. Earlier diagnosis may prevent or dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
100
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(109 citation statements)
references
References 260 publications
(222 reference statements)
1
100
0
8
Order By: Relevance
“…A number of metabolic disorders that affect the central nervous system can present in childhood, adolescence, or adulthood as a phenocopy of a major psychiatric syndrome, such as psychosis, depression, anxiety, or mania (Walterfang et al 2013). In this study, we observed that rats submitted to chronic administration of H-BCAA have a decreased sweet food intake and increased adrenal gland weight, without any alteration of body weight compared with the control group.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…A number of metabolic disorders that affect the central nervous system can present in childhood, adolescence, or adulthood as a phenocopy of a major psychiatric syndrome, such as psychosis, depression, anxiety, or mania (Walterfang et al 2013). In this study, we observed that rats submitted to chronic administration of H-BCAA have a decreased sweet food intake and increased adrenal gland weight, without any alteration of body weight compared with the control group.…”
Section: Discussionmentioning
confidence: 55%
“…Evidence from the literature shows that the causality of psychiatric illness is the result of two processes: the interruption of childhood/early adulthood neurodevelopmental trajectories in progressive illness, and the acute alteration of monoaminergic or excitatory/inhibitory neurotransmitter systems in acute or episodic illness (Walterfang et al 2013). Moreover, neurotransmitter deficiency can be a primary cause of psychiatric disorders or entrain compensatory changes in receptor expression and synaptic structure that affect brain function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the PKU-QOL (Regnault et al 2015)) address the characteristics of a particular disease or disease group. The latter are therefore the method of choice in clinical trials (Walterfang et al 2013). Since the concept of HrQoL is based on subjective experience, self-assessment using ageappropriate instruments is the gold standard (Matza et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Current research is looking at gene-environment interaction models to explain the etiology and also the variations in phenotypic expression (Chaste and Leboyer 2012). Inborn errors of metabolism are recognized as the underlying cause of several neuropsychiatric conditions (Kayser 2008;Manzi et al 2008;Walterfang et al 2013). LCHADD and other FAODs seem to elicit an increased incidence of autistic behavior (Brown et al 2014).…”
Section: Discussionmentioning
confidence: 99%